The Power of Niat Sebagai Landasan Etos Kerja Perspektif Hadis - Muhammad Ali (Universitas Islam Negeri Alauddin, 2019)
Hadith of the Prophet is one of the main sources of Islamic teaching, by which Muslims all over the world are firmly referring to in all their activities. Thus, Muslims undeniably and unquestionably follow all the rules structured within the Prophetic hadith in their day to day life. Hadith stating that all actions should be based on their intention (niat) is sound (sahi>h), on both its chain of transmission and its content. This article will explore the meaning containing within the hadith which states that all human deeds should be based on their intentions. This article will also explore the role of intention in establishing work ethos and its implication in human life.